R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst and preparation method thereof
By using R-Co2B-MoB2 catalyst in sodium borohydride hydrolysis, and using cobalt molybdate support and sodium borohydride reduction method to synthesize a rod-like catalyst, the problems of high cost of precious metal catalysts and poor activity of single metal Co-B catalysts are solved. Efficient hydrogen generation is achieved, and catalytic activity is close to the level of precious metals.
Patent Information
- Application Number
- CN202411289867.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
Precious metal catalysts are expensive, and the lack of intermetallic synergistic interaction of single metal Co-B catalysts leads to poor catalytic activity and prone to agglomeration, which limits its large-scale application in the hydrolysis of sodium borohydride hydrogen.
Using R-Co2B-MoB2 catalyst, nanocomposites with rod-like structure and rich Co vacancies were synthesized by chemical coprecipitation and sodium borohydride reduction method. Cobalt molybdate was used as a support to reduce Co-B agglomeration, improve catalytic activity, and through The strong reducing agent sodium borohydride optimizes the coupling strength between Co2B and MoB2.
The excellent catalytic activity in alkaline sodium borohydride aqueous solution was achieved, and the hydrogen evolution rate reached 7364.3mL min-1g-1, which was close to the performance of precious metal catalysts, solving the problems of expensive precious metal catalysts and poor activity of single metal Co-B catalysts. It has the potential for large-scale application.
Smart Images

Figure CN119140109A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by hydrolysis of hydrogen storage / production materials, and in particular relates to a R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst and a preparation method thereof. Background Art
[0002] Hydrogen (H2) is a high-energy-density, clean, zero-carbon-emission and sustainable energy source, and is considered a promising candidate to reduce dependence on traditional fossil fuels in the 21st century. How to achieve controllable, efficient and safe hydrogen storage and production technology is the main challenge in realizing a hydrogen economy based on fuel cells. After a lot of research, it is known that chemical hydrogen storage materials can simultaneously achieve safe hydrogen storage and controllable hydrogen, and are relatively efficient. Therefore, the development of catalytic hydrogen storage materials and hydrogen production technology has become an important research direction at present. Among various chemical hydrogen storage materials, sodium borohydride (NaBH4) has attracted much attention due to its sufficient H2 content (10.6wt.%), good stability in alkaline solutions, and non-toxicity. However, the self-hydrolysis rate of NaBH4 is slow and the kinetics are sluggish. However, under appropriate catalysis, NaBH4 can quickly and completely release all H2 at room temperature. So far, many noble metal (Ru, Pt) catalysts have been reported to show high activity in NaBH4 hydrolysis. In addition, a variety of non-noble metal catalysts, especially the combination of non-noble metals with other elements, are also considered to be an important strategy for constructing highly active catalysts. Among them, transition metal borides (TMBs) are considered to be ideal candidates for NaBH4 hydrolysis catalysts due to their metal-like electronic structures, rich bonding schemes, diverse compositions, crystal structures, and available electronic states. For example, the active sites of Co-based borides have been well determined, that is, in the presence of Co-B, NaBH4 hydrolysis can rapidly generate hydrogen.
[0003] However, the high price of precious metal catalysts limits their large-scale application in catalyzing the hydrolysis of sodium borohydride to produce hydrogen, and the single metal Co-B catalyst lacks the synergistic effect between metals and also exhibits poor catalytic activity. In addition, due to the high surface energy and magnetic agglomeration properties involved in the synthesis of Co-B, the prepared Co-B will agglomerate, which reduces the number of active sites of the catalyst and inhibits the catalytic activity. Summary of the invention
[0004] In view of the above technical problems, the present invention designs an economical, high-performance, resource-rich and large-scale applicable catalyst to drive the decomposition of hydrogen from NaBH4 water, and proposes an R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst and a preparation method thereof, so as to solve the problems that precious metal catalysts are expensive and cannot be applied on a large scale, and the single metal Co-B catalyst has poor catalytic activity due to the lack of synergistic effect between metals and easy agglomeration.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst, using a cobalt source and a molybdenum source as starting materials, and obtaining CMO-Co2B-MoB2 by chemical coprecipitation and impregnation. 2+ Precursor, and then sodium borohydride reduction method is used to synthesize R-Co2B-MoB2 nanocomposites with rod-like structure and abundant Co vacancies.
[0007] Furthermore, the specific steps of the chemical coprecipitation are as follows: the cobalt source and the molybdenum source are dispersed in water to form a uniform solution, and the two solutions are mixed and heated to react to obtain CMO nanorods.
[0008] Furthermore, the cobalt source is CoCl2·6H2O; the molybdenum source is Na2MoO4·2H2O; and the heating reaction is stirred in a 70°C water bath for 2 hours.
[0009] Furthermore, the molar ratio of the cobalt source to the molybdenum source is 1:1.
[0010] Furthermore, the specific steps of the impregnation are as follows: immersing the cobalt source and the CMO nanorods in an organic solvent, stirring to volatilize the organic solvent, and loading the cobalt source onto the CMO nanorods to obtain CMO / Co 2+ Precursor.
[0011] Furthermore, the organic solvent is acetone; and the mass ratio of the CMO nanorods to the cobalt source is 1:(1-4).
[0012] Furthermore, the sodium borohydride reduction method has the following specific steps: CMO / Co 2+ The precursor, urea and sodium chloride were ground and then reduced with sodium borohydride powder to obtain the R-Co2B-MoB2 composite material.
[0013] Furthermore, the CMO / Co 2+ The mass ratio of the precursor, urea, sodium chloride and sodium borohydride powder is 0.05:1:1:(0.1-0.3).
[0014] The present invention also provides a R-Co2B-MoB2 nanocomposite material prepared by the above preparation method.
[0015] The present invention also provides an application of the R-Co2B-MoB2 nanocomposite material in producing hydrogen by hydrolyzing sodium borohydride.
[0016] Compared with the prior art, the present invention has the following advantages and technical effects:
[0017] (1) The present invention successfully synthesized a non-precious metal R-Co2B-MoB2 catalyst with a rod-like structure and abundant Co vacancies by using a simple chemical coprecipitation, impregnation and sodium borohydride reduction method. The present invention introduced nanorod-shaped cobalt molybdate as a carrier, which reduced the aggregation of Co-B, exposed more active sites, and improved the catalytic activity. At the same time, the cobalt molybdate as a carrier not only has the ability of further structural modification, but also can provide a molybdenum source, solving the technical problem of the lack of metal synergy in a single metal.
[0018] (2) The present invention uses a strong reducing agent, sodium borohydride, for reduction, and introduces Co vacancies during the reduction process. Co vacancies, as electronic structure regulators, optimize the coupling strength between Co2B and MoB2, thereby enhancing the synergistic effect between Co2B and MoB2 and effectively promoting the conversion of BH4 - and H2O adsorption and dissociation, thereby greatly improving the catalytic activity of the catalyst.
[0019] (3) The catalyst exhibits excellent catalytic activity in alkaline sodium borohydride aqueous solution, with a hydrogen evolution rate of 7364.3 mL min -1 g -1 This excellent catalytic activity is comparable to that of precious metal-based catalysts, thus solving the technical problem that precious metal catalysts are expensive and cannot be used on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0021] Figure 1In which, a is the XRD diffraction pattern of CMO nanorods prepared in Comparative Example 1; b is the XRD spectrum of R-Co2B-MoB2 prepared in Example 1; c is the XRD spectrum of Co2B-Co3(BO3)2 prepared in Comparative Example 2; d is the XRD spectrum of Co2B-MoB2 prepared in Comparative Example 3; e is the electron paramagnetic resonance spectrum (EPR) of R-Co2B-MoB2 prepared in Example 1, Co2B-Co3(BO3)2 prepared in Comparative Example 2, and CMO nanorods prepared in Comparative Example 1; f is the Raman spectrum of R-Co2B-MoB2 prepared in Example 1, Co2B-Co3(BO3)2 prepared in Comparative Example 2, and CMO nanorods prepared in Comparative Example 1;
[0022] Figure 2 a, b, and c are respectively CMO nanorods, CMO-Co 2+ and scanning electron microscope images (SEM) of R-Co2B-MoB2; d is a transmission electron microscope image of R-Co2B-MoB2 prepared in Example 1; e is a high-resolution transmission electron microscope image (HR-TEM) of R-Co2B-MoB2 prepared in Example 1; f is a high-angle annular dark field transmission electron microscope image (HAADF-STEM) of R-Co2B-MoB2 prepared in Example 1 and the corresponding element distribution map;
[0023] Figure 3 This is the SEM image of Co2B-Co3(BO3)2 prepared in Comparative Example 2;
[0024] Figure 4 a is the Co 2p of R-Co2B-MoB2 prepared in Example 1 and Co2B-Co3(BO3)2 prepared in Comparative Example 2 3 / 2 Regional X-ray photoelectron spectroscopy; b is the Mo 3d of R-Co2B-MoB2 prepared in Example 1 5 / 2 Regional X-ray photoelectron spectrum; c is the B1s regional X-ray photoelectron spectrum of R-Co2B-MoB2 prepared in Example 1 and Co2B-Co3(BO3)2 prepared in Comparative Example 2; d is the contact angle diagram of R-Co2B-MoB2, Co2B-Co3(BO3)2 and Co2B-MoB2 prepared in Example 1, Comparative Example 2 and Comparative Example 3;
[0025] Figure 5a and b are respectively the relationship between the equivalent H2 per mole of sodium borohydride and time when the composite materials prepared in Example 1 and Comparative Examples 1-3 are used as catalysts, and the corresponding specific hydrogen evolution rate (HGR) value; c and d are respectively the relationship between the equivalent H2 per mole of sodium borohydride and time when the composite materials prepared in Example 1, Example 2 and Comparative Example 4 are used as catalysts, and the corresponding specific hydrogen evolution rate (HGR) value; e and f are respectively the relationship between the equivalent H2 per mole of sodium borohydride and time when the composite materials prepared in Example 1 and Example 3 are used as catalysts, and the corresponding specific hydrogen evolution rate (HGR) value;
[0026] Figure 6 a and b respectively represent the change of the amount of hydrogen produced per mole of sodium borohydride at different temperatures with time when the composite material prepared in Example 1 is used as a catalyst and the corresponding Arrhenius plot; c and d respectively represent the change of the amount of hydrogen produced per mole of sodium borohydride during a single cycle with time when the composite material prepared in Example 1 is used as a catalyst and the HGR value after each cycle. DETAILED DESCRIPTION
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] A preparation method of a R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst includes chemical coprecipitation, impregnation and sodium borohydride reduction methods. The chemical coprecipitation is to mix a cobalt source and a molybdenum source in a water bath at a certain temperature to obtain cobalt molybdate (CoMoO6·0.9H2O) nanorods (CMO nanorods); the impregnation is to immerse the CoMoO6·0.9H2O nanorods and CoCl2·6H2O in an acetone solution to obtain CMO-Co 2+ Precursor; finally, CMO-Co 2+ The precursor is reduced to obtain the R-Co2B-MoB2 composite material.
[0033] The CMO nanorods are prepared by dropping an aqueous solution of ammonium molybdate (Na2MoO4·2H2O) into an aqueous solution of cobalt chloride (CoCl2·6H2O), followed by stirring for 2 hours in a water bath at 70°C, and finally collecting by centrifugation, washing three times with water and ethanol, and drying at 60°C.
[0034] The mass ratio of the CMO nanorods to CoCl2·6H2O is 1:4 or 1:1.
[0035] The sodium borohydride reduction method is to reduce CMO-Co 2+ The precursor, urea and sodium chloride are fully ground and then placed in an oven for drying. The dried powder is sprinkled with sodium borohydride powder for reduction. After complete reduction, water is added for centrifugal collection, washed with water and ethanol, and dried.
[0036] The CMO / Co 2+ The mass ratio of the precursor, urea, sodium chloride and sodium borohydride powder is 0.05:1:1:(0.1-0.3), and the preferred amount of sodium borohydride powder is 0.1, 0.2g or 0.3g, that is, the mass ratio is 0.05:1:1:0.1, 0.05:1:1:0.2 or 0.05:1:1:0.3.
[0037] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0038] The raw materials used in the present invention are all purchased from the market.
[0039] The technical solution of the present invention is further illustrated by the following embodiments.
[0040] Example 1
[0041] Preparation of R-Co2B-MoB2 composite materials:
[0042] (1) Preparation of CoMoO6·0.9H2O (CMO) nanorods: 5 mmol CoCl2·6H2O was weighed and dissolved in 30 mL H2O, and 5 mmol Na2MoO4·2H2O was weighed and dissolved in 30 mL H2O. Then, the Na2MoO4·2H2O solution was added dropwise to the CoCl2·6H2O solution, and the mixture was stirred at 70°C in a water bath for 2 h. Finally, the mixture was collected by centrifugation, washed with water and ethanol three times, and dried at 60°C for 12 h to obtain CMO nanorods.
[0043] (2) Preparation of CMO-Co 2+ : 30 mg CMO nanorods and 120 mg CoCl2·6H2O were dissolved in 10 mL acetone and stirred until the acetone was completely volatilized. The cobalt source was loaded onto the CMO nanorods to obtain CMO / Co 2+ Precursor;
[0044] (3) Preparation of R-Co2B-MoB2 (R represents high Co content, and its actual Co content is 53.2 wt. % as determined by ICP-MS): 50 mg CMO-Co 2+ The precursor, 1 g NaCl and 1 g urea were put into a mortar and ground thoroughly for 10 min until there was no particle feeling. Then the pink mixture was placed in a 60 °C oven and dried for 4 h. Then 0.2 g sodium borohydride powder was added, stirred evenly and allowed to stand for complete reaction. Finally, water was added and the mixture was centrifuged after there were no bubbles. The mixture was washed with water and ethanol three times and dried overnight at 70 °C in vacuum.
[0045] Example 2
[0046] When CMO / Co 2+ Preparation of R-Co2B-MoB2 composite material when the mass ratio is 1:1:
[0047] Same as Example 1, except that
[0048] Step (2) is specifically as follows: 30 mg of CMO and 30 mg of CoCl2·6H2O are dissolved in 10 mL of acetone, stirred until the acetone is completely volatilized, and the cobalt source is loaded onto the CMO nanorods. That is, the mass ratio of CMO nanorods to CoCl2·6H2O is 1:1.
[0049] Example 3
[0050] Preparation of R-Co2B-MoB2 composite materials with different sodium borohydride dosages:
[0051] Same as Example 1, except that, in step (3): weigh 50 mg CMO-Co 2 Precursor + , 1g NaCl and 1g urea are put into a mortar, ground thoroughly, and then put into an oven at 60℃ to dry for 4h. Then, 0.1g and 0.3g sodium borohydride powder are added respectively, stirred evenly and allowed to stand for complete reaction. Finally, water is added, and centrifuged after there are no bubbles. Wash with water and ethanol three times, and dry overnight at 70℃ in vacuum.
[0052] Comparative Example 1
[0053] Preparation of CoMoO6·0.9H2O (CMO) nanorods:
[0054] Weigh 5 mmol CoCl2·6H2O and dissolve it in 30 mL H2O. Weigh another 5 mmol Na2MoO4·2H2O and dissolve it in 30 mL H2O. Then, add the Na2MoO4·2H2O solution dropwise into the CoCl2·6H2O solution, stir in a 70°C water bath for 2 h, collect by centrifugation, wash three times with water and ethanol, and dry at 60°C for 12 h to obtain CMO nanorods.
[0055] Comparative Example 2
[0056] Preparation of Co2B-Co3(BO3)2 composite materials:
[0057] Weigh 50 mg CoCl2·6H2O, 1 g NaCl and 1 g urea into a mortar, grind them thoroughly, and then put them into an oven at 60°C for 4 h. Then add 0.2 g sodium borohydride powder, stir evenly and let it stand for complete reaction. Finally, add water, centrifuge after there are no bubbles, wash with water and ethanol three times, and dry them at 70°C in vacuum overnight to obtain a Co2B-Co3(BO3)2 composite material.
[0058] Comparative Example 3
[0059] Preparation of Co2B-MoB2 composite materials:
[0060] (1) Preparation of CoMoO6·0.9H2O (CMO) nanorods: 5 mmol CoCl2·6H2O was weighed and dissolved in 30 mL H2O, and 5 mmol Na2MoO4·2H2O was weighed and dissolved in 30 mL H2O. Then, the Na2MoO4·2H2O solution was added dropwise to the CoCl2·6H2O solution, and the mixture was stirred at 70°C in a water bath for 2 h. Finally, the mixture was collected by centrifugation, washed with water and ethanol three times, and dried at 60°C for 12 h to obtain CMO nanorods.
[0061] (2) Preparation of Co2B-MoB2: Weigh 50 mg CMO, 1 g NaCl and 1 g urea into a mortar and grind thoroughly. Then, dry them in an oven at 60°C for 4 h. Then, add 0.2 g sodium borohydride powder, stir evenly and let stand for complete reaction. Finally, add water and centrifuge after there are no bubbles. Wash with water and ethanol three times, and dry them at 70°C in vacuum overnight to obtain a Co2B-MoB2 composite material (the actual Co content was 45.1 wt. % as determined by ICP-MS).
[0062] Comparative Example 4
[0063] Different CMO / Co 2+ Preparation of R-Co2B-MoB2 composite materials under mass ratio:
[0064] Same as Example 1, except that
[0065] Method 1: Step (2) is as follows: 30 mg CMO and 240 mg CoCl2·6H2O are dissolved in 10 mL acetone, stirred until the acetone is completely volatilized, and the cobalt source is loaded onto the CMO nanorods. That is, the mass ratio of CMO nanorods to CoCl2·6H2O is 1:8.
[0066] Method 2: Step (2) is specifically as follows: 120 mg CMO and 30 mg CoCl2·6H2O are dissolved in 10 mL acetone, stirred until the acetone is completely volatilized, and the cobalt source is loaded onto the CMO nanorods, that is, the mass ratio of CMO nanorods to CoCl2·6H2O is 4:1.
[0067] Characterization:
[0068] The composite materials prepared in the above Examples 1-3 and Comparative Examples 1-4 were subjected to characterization tests on structure, composition, morphology and surface chemical state. Specifically:
[0069] 1. The structure of the prepared composite material was determined using an X-ray diffractometer (XRD, Rigaku 13d / Max 2500V / PC, Japan).
[0070] Figure 1 Figure a is the XRD diffraction pattern of the CMO nanorods prepared in Comparative Example 1. It can be seen that the CMO nanorods are consistent with the standard card of CoMoO6·0.9H2O (JCPDS: 14-0086), indicating that the CMO nanorods were successfully synthesized.
[0071] Figure 1Figure b is the XRD spectrum of R-Co2B-MoB2 prepared in Example 1. It can be seen that the XRD spectrum of R-Co2B-MoB2 has a broad peak centered at 2θ≈34.0° and 45.4°, which matches well with MoB2 (JCPDS: 06-0682) and Co2B (JCPDS: 25-0241). Its broad peak indicates that the crystallinity of the catalyst is weak, which is caused by a violent reduction reaction during reduction with sodium borohydride.
[0072] Figure 1 In c, the XRD pattern of Co2B-Co3(BO3)2 prepared in Comparative Example 2 is shown. It can be seen that the XRD pattern of Co2B-Co3(BO3)2 is consistent with the known patterns of Co2B (JCPDS: 25-0241) and Co3(BO3)2 (JCPDS: 25-0102). Figure 1 The results are consistent, indicating that Co2B-Co3(BO3)2 was successfully synthesized.
[0073] Figure 1 Figure d is the XRD spectrum of Co2B-MoB2 prepared in comparative example 3. It can be seen that the diffraction peaks of Co2B-MoB2 are consistent with the diffraction peaks in the standard cards of Co2B (JCPDS: 25-0241) and MoB2 (JCPDS: 06-0682), confirming the formation of Co2B-MoB2.
[0074] Figure 1 Figure e is the electron paramagnetic resonance spectra (EPR) of R-Co2B-MoB2 prepared in Example 1, Co2B-Co3(BO3)2 prepared in Comparative Example 2, and CMO nanorods prepared in Comparative Example 1; it can be seen that the composite material has an electron paramagnetic resonance (EPR) signal at g=2.15, which is related to cation vacancies, proving the existence of Co vacancies. The signal intensity of the R-Co2B-MoB2 composite material is the largest, indicating the highest vacancy concentration.
[0075] Figure 1 f is the Raman spectra of R-Co2B-MoB2 prepared in Example 1, Co2B-Co3(BO3)2 prepared in Comparative Example 2, and CMO nanorods prepared in Comparative Example 1. It can be seen that the Raman spectra at 334, 358, 852, and 933 cm -1 The peaks at 188, 462, 506, 608 and 665 cm-1 in the Raman spectra of R-Co2B-MoB2 and Co2B-Co3(BO3)2 are respectively attributed to the Co-O-Mo, O-Mo-O and Mo-O-Co bonds of CMO, further confirming that CMO was successfully synthesized. -1 The five peaks correspond to the typical Raman active modes A and B of cobalt oxide. 1g 、F2g 、F 2g 、E g and F 2g . Metal borides spontaneously oxidize when exposed to air to form surface oxides, thus forming a core-shell structure (metal boride@metal oxide). Therefore, the Raman spectrum mainly detects the characteristic peaks of cobalt oxide. It is worth noting that the red shift of the Raman peak indicates that the crystal structure is short-range ordered, which is in good agreement with the results of XRD. 188cm -1 The peak intensity at 608 and 188 cm-1 decreased significantly, indicating that more defect sites were formed after the introduction of CMO. -1 The binding energies at and are respectively attributed to the octahedral site (CoO6) and tetrahedral coordination (CoO4) of the multivalent cobalt oxide. 188 / I 608 ) to evaluate the CoO4 / CoO6 ratio. R-Co2B-MoB2 has an I of 0.45 compared to Co2B-Co3(BO3)2 (0.49). 188 / I 608 The ratio decreases, which indicates that Mo first occupies the tetrahedral sites of Co3O4 under the reduction of sodium borohydride, which leads to the 2+ Vacant seat.
[0076] 2. The morphology of the catalyst was elucidated using scanning electron microscopy (SEM, FEIQuanta 200FEG) and transmission electron microscopy (TEM, JEM-2100F).
[0077] Figure 2 a, b, and c are respectively CMO nanorods, CMO-Co 2+ Scanning electron microscope images (SEM) of CMO nanorods and R-Co2B-MoB2; the SEM image in Figure a shows that CMO nanorods were successfully prepared, showing a smooth nanorod-like structure. As can be seen from Figure b, after impregnation, the CMO nanorods were uniformly wrapped by CoCl2·6H2O particles. As can be seen from Figure c, after reduction, R-Co2B-MoB2 still maintains the nanorod morphology, and it can be seen that irregularly shaped nanoparticles are also attached to the surface of the nanorods.
[0078] Figure 2 d in the figure is the transmission electron microscope image of R-Co2B-MoB2 prepared in Example 1; Figure 2 e in FIG. 1 is a high-resolution transmission electron microscopy image (HR-TEM) of R-Co2B-MoB2 prepared in Example 1; Figure 2Figure f is a high-angle annular dark field transmission electron microscopy (HAADF-STEM) image of R-Co2B-MoB2 prepared in Example 1 and the corresponding element distribution map. As can be seen from Figure d, R-Co2B-MoB2 still maintains the form of nanorods, and it can be seen that irregularly shaped nanoparticles are also attached to the surface of the nanorods. It is worth noting that the one-dimensional rod-like structure can be used as a high-speed way to increase the ion diffusion rate, thereby promoting the hydrolysis of sodium borohydride. HR-TEM analysis shows (Figure e) that the lattice fringe spacing is 0.198nm and 0.182nm, corresponding to the (211) and (112) crystal planes of R-Co2B-MoB2, respectively. The lattice spacing of 0.200nm corresponds to the (101) crystal plane of MoB2. High-angle annular dark field scanning transmission electron microscopy and element distribution maps confirm that the Co, Mo and B elements are uniformly distributed throughout the structure (Figure f).
[0079] Figure 3 This is the SEM image of Co2B-Co3(BO3)2 prepared in Comparative Example 2. Figure 3 The SEM image of Co2B-Co3(BO3)2 is shown, and due to its magnetic properties, a large number of connected nanosheets are aggregated into blocks.
[0080] 3. Electron paramagnetic resonance spectrometer (EPR, Bruker) was used to directly identify Co vacancies. Raman spectra were obtained using a Renishaw instrument with visible laser (k = 532nm). X-ray photoelectron spectroscopy (XPS, Japan JPS-9010TR photoelectron spectrometer) analyzed the surface element valence state of the composite material. The water contact angle was measured using an optical contact angle meter (Dataphysics-OCA20).
[0081] Figure 4 a is the Co 2p of R-Co2B-MoB2 prepared in Example 1 and Co2B-Co3(BO3)2 prepared in Comparative Example 2 3 / 2 Regional X-ray photoelectron spectroscopy; Figure 4 b is the Mo 3d of R-Co2B-MoB2 prepared in Example 1 5 / 2 Regional X-ray photoelectron spectroscopy; Figure 4 c is the B1s region X-ray photoelectron spectra of R-Co2B-MoB2 prepared in Example 1 and Co2B-Co3(BO3)2 prepared in Comparative Example 2; Figure 4 Figure d is the contact angle diagram of R-Co2B-MoB2, Co2B-Co3(BO3)2 and Co2B-MoB2 prepared in Example 1, Comparative Example 2 and Comparative Example 3. As can be seen from Figure a, the high-resolution Co2p 3 / 2The spectrum is divided into four peaks. The peak at 778.6 eV corresponds to Co-B, and 780.9 eV, 782.5 eV and 786.0 eV correspond to Co 3+ 、Co 2+ and satellite peaks (Sat.), indicating the presence of oxides on the surface, which is consistent with the Raman spectroscopy results. 3+ and Co 2+ The area ratio of Co2B-Co3(BO3)2 is 1.32, which is significantly larger than that of Co2B-Co3(BO3)2 (1.03), which confirms that there are more Co vacancies in R-Co2B-MoB2. 2+ The formation of vacancies is thermodynamically slower than that of Co 3+ The formation of vacancies is more favorable. Therefore, most cobalt vacancies are Co 2+ Vacancies. The Co-B in R-Co2B-MoB2 has a negative shift of 0.16 eV compared with Co2B-Co3(BO3)2, indicating that after introducing more Co vacancies, there is a strong electronic interaction between the two components of Co2B and MoB2, which can effectively reduce the reaction energy barrier of the R-Co2B-MoB2 catalyst, thereby increasing the catalytic reaction rate. As can be seen from Figure b, Mo3d 5 / 2 The spectra in this region can be fitted to Mo-B (228.7 eV), Mo 4+ (230.5eV) and Mo 6+ (232.3eV). Figure c shows that R-Co2B-MoB2 and Co2B-Co3(BO3)2 samples have two obvious peaks at around 188.1eV and 191.9eV, which correspond to MB bonds and BO bonds, respectively. The adsorption of H2O by the catalyst is crucial for the hydrolysis of NaBH4. Therefore, the present invention carried out water contact angle measurements to study the wettability of Co2B-MoB2 and Co2B-Co3(BO3)2. As shown in Figure d, the contact angle of R-Co2B-MoB2 is 51.4°, which is smaller than Co2B-Co3(BO3)2 (64.6°) and Co2B-MoB2 (58.0°), indicating that R-Co2B-MoB2 doped with Mo and more Co is much more hydrophilic than Co2B-Co3(BO3)2 and Co2B-MoB2. It is well known that the surface wettability of a material depends largely on its surface composition and morphological structure. Therefore, the above different wetting behaviors can be explained from their different morphologies and compositions, that is, the unique rod-like structure and the introduction of Mo-B help to improve the hydrophilicity of R-Co2B-MoB2. The increase in hydrophilicity is beneficial to the transport and activation of NaBH4 and H2O, thereby promoting the water decomposition of NaBH4 for hydrogen.
[0082] Sodium borohydride hydrolysis performance test:
[0083] (1) Hydrogen evolution rate test: 25 mL of 150 mM NaBH4 solution (containing 0.4 wt.% NaOH) was measured with a pipette in a 100 mL three-necked flask and stirred in a 25°C water bath for 30 min until the reading of the electronic balance stabilized. Then 10 mg of the catalyst prepared in Examples 1-3 and Comparative Examples 1-4 was weighed and immediately put into the above solution. The generated hydrogen was measured by drainage technology, and the drainage system was connected to a computer to record the instantaneous change in water volume. The computer recorded it every 10 seconds, and finally the hydrogen evolution rate (HGR) was obtained by the change in water volume over time.
[0084] The calculation formula of hydrogen evolution rate (HGR) is:
[0085]
[0086] in, is the volume of water discharged, t is the total reaction time, and m is the amount of catalyst added.
[0087] (2) Activation energy test: The hydrogen evolution rates of the catalysts prepared in Example 1 and Comparative Example 2 were tested using a hydrogen evolution rate test device at 298K, 303K, 308K, 313K, and 318K, respectively, and the activation energy of the corresponding catalysts was finally calculated using the Arrhenius equation. The Arrhenius equation is:
[0088] lnκ=lnA-E a / RT
[0089] Among them, κ, A, R, and T represent the reaction rate constant, pre-exponential factor, molar gas constant, and thermodynamic temperature (K), respectively.
[0090] (3) Catalyst reusability test: After completing a hydrogen evolution rate test, 150 mM NaBH4 powder was added to the flask again, and the test was continued until no bubbles were generated, and new sodium borohydride was added again. This was repeated five times in total. The present invention tested the reusability of the catalyst prepared in Example 1.
[0091] Figure 5 a and b are the relationship diagram of the equivalent H2 per mole of sodium borohydride and time when the composite materials prepared in Example 1 and Comparative Examples 1-3 are used as catalysts, as well as the corresponding specific hydrogen evolution rate (HGR) value; it can be seen from the figure that R-Co2B-MoB2 has the highest HGR value, which confirms that the R-Co2B-MoB2 composite material prepared in Example 1 of the present invention has excellent catalytic activity.
[0092] Figure 5c and d are the relationship between the equivalent H2 per mole of sodium borohydride and time and the corresponding specific hydrogen evolution rate (HGR) value when the composite materials prepared in Example 1, Example 2 and Comparative Example 4 are used as catalysts; it can be seen from the figure that the optimal mass ratio of CMO and CoCl2·6H2O is 1:4.
[0093] Figure 5 Figures e and f are the relationship between the equivalent H2 per mole of sodium borohydride and time when the composite materials prepared in Example 1 and Example 3 are used as catalysts, and the corresponding specific hydrogen evolution rate (HGR) value; it can be seen from the figure that the optimal reducing agent usage is 0.2g.
[0094] Figure 6 a and b in the figure are the change of the amount of hydrogen produced per mole of sodium borohydride at different temperatures with time when the composite material prepared in Example 1 is used as the catalyst and the corresponding Arrhenius plot. It can be seen from Figures a and b that the release rate of H2 increases with the increase of the reaction temperature. The activation energy of R-Co2B-MoB2 calculated according to the Arrhenius equation is 44.4 kJ mol -1 , lower than Co2B-Co3(BO3)2(45.5kJ mol -1 ), indicating a strong synergistic effect between Co2B and MoB2 from a kinetic point of view. The reusability of the catalyst is another key parameter for its practical application. The continuous cycle test of NaBH4 hydrolysis was carried out on the R-Co2B-MoB2 catalyst at 298K.
[0095] Figure 6 In the figure c and d are respectively the variation of the amount of hydrogen produced per mole of sodium borohydride over time during a single cycle when the composite material prepared in Example 1 is used as a catalyst and the HGR value after each cycle. It can be seen that after the catalyst is reused 5 times, the catalytic activity decreases slightly, indicating that the R-Co2B-MoB2 catalyst has good reusability.
[0096] In addition, the performance of the R-Co2B-MoB2 catalyst prepared in Example 1 of the present invention was compared with other existing noble metal-based catalysts, and the comparison results are shown in Table 1:
[0097] Table 1
[0098]
[0099] It can be seen from Table 1 that the hydrogen evolution performance of the R-Co2B-MoB2 catalyst prepared in Example 1 is slightly lower than that of Pt / CeO2-Co7Ni2O and slightly higher than that of Ru-CoP@GO, but much higher than that of other precious metal-based catalysts, indicating that the non-precious metal R-Co2B-MoB2 catalyst is comparable to or even higher than that of precious metal-based catalysts, and is therefore expected to replace precious metal-based catalysts.
[0100] In summary, the non-precious metal R-Co2B-MoB2 sodium borohydride hydrolysis catalyst prepared in Example 1 of the present invention exhibits excellent catalytic activity, which is comparable to or even better than precious metal catalysts. This excellent performance is attributed to the synergistic effect between the Co2B and MoB2 components and the regulation of the electronic structure of R-Co2B-MoB2 by Co vacancies. In addition, the low activation energy and good reusability make it have the potential for large-scale practical applications.
[0101] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a catalyst for producing hydrogen by hydrolysis of sodium borohydride R-Co2B-MoB2, characterized in that: CMO-Co was obtained by chemical coprecipitation and impregnation using cobalt source and molybdenum source as starting materials. 2+ Precursor, and then sodium borohydride reduction method is used to synthesize R-Co2B-MoB2 nanocomposites with rod-like structure and abundant Co vacancies.
2. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 1, characterized in that: The specific steps of the chemical coprecipitation are as follows: the cobalt source and the molybdenum source are dispersed in water to form a uniform solution, and the two solutions are mixed and heated to react to obtain CMO nanorods.
3. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 2, characterized in that: The cobalt source is CoCl2·6H2O; the molybdenum source is Na2MoO4·2H2O; and the heating reaction is carried out by stirring in a water bath at 70°C for 2 hours.
4. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 2, characterized in that: The molar ratio of the cobalt source to the molybdenum source is 1:
1.
5. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 2, characterized in that: The specific steps of the impregnation are as follows: immersing the cobalt source and the CMO nanorods in an organic solvent, stirring to volatilize the organic solvent, and loading the cobalt source onto the CMO nanorods to obtain CMO / Co 2+ Precursor.
6. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 5, characterized in that: The organic solvent is acetone; the mass ratio of the CMO nanorods to the cobalt source is 1:(1-4).
7. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 5, characterized in that: The specific steps of the sodium borohydride reduction method are as follows: 2+ The precursor, urea and sodium chloride were ground and then reduced with sodium borohydride powder to obtain the R-Co2B-MoB2 composite material.
8. The method for preparing the R-Co2B-MoB2 sodium borohydride hydrolysis hydrogen production catalyst according to claim 7, characterized in that: The CMO / Co 2+ The mass ratio of the precursor, urea, sodium chloride and sodium borohydride powder is 0.05:1:1:(0.1-0.3).
9. A R-Co2B-MoB2 nanocomposite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the R-Co2B-MoB2 nanocomposite material as claimed in claim 9 in producing hydrogen by hydrolysis of sodium borohydride.
